Microsporia in Young Children: Clinical Cases - Alexey B. Yakovlev; Aleksandra S. Polonskaya; Larisa S. Kruglova ("Paediatrician" Publishers LLC, 2022)
Background. Microsporia is a zooanthroponotic mycosis of skin and hair caused by fungi genus Microsporum. Microsporia is most common among children, including infants. The microsporia incidence has slow steady increase over recent years.Clinical cases description. Follow-up results of two children of different ages (younger/older than 1 year) with microsporia are presented. Successful management approach is shown. Major limitations of drug therapy in infants as well as common therapeutic errors were analyzed.Conclusion. Diagnosis and management of microsporia in infants and young children is a challenging task. Major errors in microsporia management in patients of these age groups are associated with peculiarities of clinical picture as well as limited variations of drugs that are appropriate for the requirements on efficacy and safety of therapy among young children.